1979
DOI: 10.1002/cpt1979255part1579
|View full text |Cite
|
Sign up to set email alerts
|

Excretion of chlordecone by the gastrointestinal tract: Evidence for a nonbiliary mechanism

Abstract: Workers exposed to chlordecone (Kepone), a toxic organochlorine pesticide, excreted larger amounts of chlordecone in bile than in stool, suggesting that it may undergo enterohepatic recirculation, We found in a single subject that equal amounts of chlordecone and of its reduced metabolite, chlordecone alcohol, were excreted in bile at a rate four times as great as in stool. When biliary contents were diverted from the intestine through a T tube, fecal excretion of chlordecone alcohol was abolished, presumably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 5 publications
1
16
0
Order By: Relevance
“…Excretion data obtained from humans exposed to chlordecone and rats that were administered the compound are consistent with this route as a significant excretory pathway (58,59). The authors observed that fecal excretion of chlordecone was maintained or increased when bile flow was diverted relative to that seen while bile flow was intact.…”
Section: Excretionsupporting
confidence: 56%
“…Excretion data obtained from humans exposed to chlordecone and rats that were administered the compound are consistent with this route as a significant excretory pathway (58,59). The authors observed that fecal excretion of chlordecone was maintained or increased when bile flow was diverted relative to that seen while bile flow was intact.…”
Section: Excretionsupporting
confidence: 56%
“…Chlordecone and chlordecone alcohol (chlordecol) are excreted in the bile and eliminated via the feces of humans occupationally exposed to chlordecone Cohn et al, 1978;Boylan et al, 1979;Guzelian et al, 1981). A substantial enterohepatic recirculation of chlordecone exists, however, that curtails its excretion ( Cohn et al, 1978;Boylan et al, 1979;Guzelian et al, 1981 ).…”
Section: Distributionmentioning
confidence: 99%
“…A substantial enterohepatic recirculation of chlordecone exists, however, that curtails its excretion ( Cohn et al, 1978;Boylan et al, 1979;Guzelian et al, 1981 ). Only 5-10% of the biliary chlordecone entering the lumen of the duodenum appeared in the feces (Cohn et al, 1978;Guzelian et al, 1981).…”
Section: Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…This nonbiliary mechanism has been observed for OCs, such as chlordecone. Fecal excretion of chlordecone was found to be the same in rats with or without biliary diversion [11]. Presumably OCs enter the intestine by secretion out of the enterocyte, or by turnover of enterocytes that contain significant amounts of OCs.…”
Section: Organochlorine Compound Entry Into the Intestinementioning
confidence: 95%